Manual material handling in the supermarket sector. Part 1: Joint angles and muscle activity of trapezius descendens and erector spinae longissimus. (April 2021) - Skals, Sebastian; Bláfoss, Rúni; Andersen, Michael Skipper; de Zee, Mark; Andersen, Lars Louis
Abstract: Work-related musculoskeletal disorders are highly prevalent in the supermarket sector with manual material handling being one of the most commonly identified occupational risk factors. This cross-sectional study applied inertial motion capture and electromyography (EMG) to measure full-body kinematics and muscle activity of trapezius descendens and erector spinae longissimus during 50 manual material handling tasks performed by 17 workers in two supermarkets. The handling of bread and cucumbers to high shelf heights showed the highest trapezius muscle activity (from 47% to 59% peak normalized EMG), while the handling of bananas as well as lifting milk, bread and cucumbers from low to high positions showed the highest erector spinae activity (from 59% to 71%). Twenty-two tasks involved flexing the shoulders and trunk more than 90° and 50°, respectively. Based on these results, several manual handling practices in supermarkets should be reconsidered to reduce the physical work demands. Highlights: Field analysis of common manual material handling activities in two supermarkets. Cucumbers and bread required highest muscular efforts for the shoulder/neck. Bananas, milk, cucumbers and bread required highest efforts for the lower back. Large proportion of the analyzed tasks involved undesirable working postures. Handling practices should be reconsidered to reduce physical work demands.